From Michael and Teca: two unpublished letters to Hubert Jennings - Brown, Susan Margaret (Pessoa Plural, 2015)
What follows is the transcription of two letters written to Hubert D. Jennings, one by Pessoa's half-brother Michael (born Luiz Miguel) Nogueira Rosa, the other by Pessoa's half-sister Henriqueta Madelena Dias, known to her friends as "Teca." Together they offer the only evidence we have in the Jennings archive of a correspondence with Pessoa's family. Michael's letter is largely a response to Jennings's questions regarding his translations of Pessoa, Pessoa's English poems, and the prospect of Jennings's own book on the poet; Teca's is full of personal memories of time spent in South Africa and at the family residence on Rua Coelho da Rocha. The letters complement each other: one adds to our knowledge of how Pessoa's estate was managed; the other gives us an account of Pessoa's daily routine upon his return to Lisbon in 1905. A general introduction and explanatory notes accompany the transcription of the letters.